2004
DOI: 10.2113/gscanmin.42.5.1583
|View full text |Cite
|
Sign up to set email alerts
|

Silicate Melt Inclusions in Porphyry Copper Deposits: Identification and Homogenization Behavior

Abstract: Silicate melt inclusions are ubiquitous in phenocrysts in porphyry copper deposits. Compared to melt inclusions in other igneous environments, those in porphyry copper deposits are more difficult to recognize and analyze, for a variety of reasons. The inclusions are usually partially to completely crystallized or altered by hydrothermal fluids, resulting in a dark, granular appearance. In this study, a protocol for identifying and homogenizing crystallized melt-inclusions from porphyry copper deposits is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 38 publications
1
42
0
2
Order By: Relevance
“…Also, the optics improved if the crystal was free of matrix glass. As previously noted by [15], groundmass adhering to phenocrysts affects the optics because it consists of dark recrystallized glass that generally melts before the MI has completely homogenized and flows around the crystal (or through fractures in the crystal) causing the optics to deteriorate. In order to remove matrix glass from the crystals before heating experiments, some authors have suggested that the samples should be placed in concentrated hydrofluoric acid solution for several seconds [15,36], but this was not done for the phenocrysts studied here.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Also, the optics improved if the crystal was free of matrix glass. As previously noted by [15], groundmass adhering to phenocrysts affects the optics because it consists of dark recrystallized glass that generally melts before the MI has completely homogenized and flows around the crystal (or through fractures in the crystal) causing the optics to deteriorate. In order to remove matrix glass from the crystals before heating experiments, some authors have suggested that the samples should be placed in concentrated hydrofluoric acid solution for several seconds [15,36], but this was not done for the phenocrysts studied here.…”
Section: Resultsmentioning
confidence: 94%
“…A few of the MI could not be heated to homogenization, either because the optics deteriorated before homogenization was achieved or, in one case, because the crystals began to fracture and break into smaller pieces owing to the high internal pressures generated in the volatile-rich MI during heating. For such samples, it is necessary to heat the MI in a pressurized vessel to eliminate or minimize decrepitation and/or leakage [14,15,24,35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations